Pengaruh pH Dan Waktu Pada Pengolahan Limbah Cair Cpo Dengan Proses Ozonasi - Novermen Novermen; Syarfi Syarfi; Jecky asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
There have been several methods widely developed for crude palm oil (CPO) extraction from palm oil fruits, which produces liquid waste around 60% from the total production capacity. This liquid waste contains organic over than maximum limit, which is permitted by environmental quality standards of ministerial decision LH No. KEP-51/ MENLH/ 1995. one of the technologies that can be used is the Ozonation technology. It is done by contacting Palm Oil Mill Effluent (POME) with ozone. Ozon is produced from the ozone generator with 18 watt power, with concentration 0,1068 mg/s. Ozone serves to reduce chemical oxygen demand (COD), oil, and total solid (TTS) in crude palm oil factory. This research was conducted with variation of PH, 8,10, and 12 with NaOH addition and variation of time 10, 20, 30, 40 minutes. The research finding obtained that the efficiency chemical oxygen demand (COD) could reach maximum 90 % , with PH 8 in 40 minutes. Keyword: COD, POM, Ozonation, Total solid